Family Planning vs. Women's Rights: The Case of Quinacrine Sterilization in Chile - Martinez, Jazmin
Since its development during the 1970s in Chile, 100,000 women have been chemically sterilized with Quinacrine worldwide, which is still not FDA approved and has been banned by the WHO. While clinical research exists about this method, conditions that led to the emergence of this particular sterilization method have gone unexplored. The study explored how it was that this method came about under the rule of an authoritarian regime which implemented pronatalist policies. This phenomenon was then used to explore the broader concern regarding the difficulties of implementing comprehensive reproductive rights in developing countries with complex cultures and politics. Chile also demonstrates the dangers associated with trying to implement solely reproductive rights without considering the larger aspects of women's rights. Furthermore, the article examined the reasons behind a push for sterilization as a method of birth control in developing countries in place of less hazardous methods. And lastly, the study examined the degree to which women are left with no other choice but to opt for experimental forms of contraception such as Quinacrine. The case of Chile is more than forced eugenics on poor women, although that is part of the phenomenon, the study focused on the obstacles third world women have in gaining full women's rights.